Register Realization in the Writing of 8th Grade Students of SMP Kesatrian Semarang (A Comparative Study between Dialogue and Recount Text) - Maulina, Azizah Ezard ((JELE) Journal Of English Language and Education, 2015)
This research aimed at comparing the contextual description of the field, tenor,and mode between written dialogue and recount text in the writing of the 8th grade students of SMP Kesatrian 1 Semarang. The next was to find which text was the student‟s major and find the reason why register realization in dialogue and recount text is the same or different. This was a qualitative research by employing descriptive comparative method. The corpus of the data of this research were written dialogue and recount text in the writing of the 8th grade students of SMP Kesatrian 1 Semarang. The results showed as follows: (1) the production of „experiential domain found‟, „short term goal‟, and „long term goal‟ in the written dialogue texts were more various than in the recount texts; (2) The production of agentive or societal roles, status, and socialdistance in dialogue texts were also more various than in recount texts; (3) The role of language, type of interaction, and the rhetorical trust in the written dialogues were different from the recount texts ( Meanwhile the medium and the channel of both texts were the same); (4) The students produced more various features in terms of contextual description of the field, tenor, and mode in written dialogues than in recount texts; (5) The similarities between written dialogues and recount texts found in the terms of medium and channel. Meanwhile the differences between them were found in the other terms (experiential domain etc.). In conclusion, the students were more major inmaking written dialogue than recount text.Keywords: Mood, Register, Theme, Transitivity, Recount Text